Environmentally Oriented Chemistry Practical Worksheets to Improve Conservation Character and Environmental Literacy - Nuswowati, Murbangun; Kadarwati, Sri; Susatyo, Eko Budi; Huda, Nuril; Kolilah, Liluk; Dewi, Silmi Dalila Millatina; Zahro, Ainu Ilmiatuz; Azzahra, Yasmin (Universitas Negeri Semarang, 2023)
Management of chemistry practicum implementation has become a problem center that must be faced. This is caused by limited equipment and materials available in the laboratory, shortage of laboratory personnel , as well as its height costs required to carry out the practicum. Apart from that, chemistry practicum requires a high level of creativity from Chemistry teachers, well when they have to organize practicums independently and in classical learning for students. Therefore , guidance and mentoring _ from the service team is very important to help Chemistry teachers in developing their learning materials. This assistance takes place from June 22 to August 16 2022, starting with coordination between chairman of the MA Chemistry MGMP with the UNNES service team. The aim of the Community Service Program (PPM) is to build conservation character and environmental literacy among Chemistry teachers, also involving students, and of course MA students in Semarang. To date, there have been 2 environmentally oriented Chemistry Practical Worksheets created successfully , which is the result collaboration between one teacher and one student. At the end of August, we will proceed with further implementation steps . Results _ from this service activity will be published in a national journal accredited SINTA 3-6 . The process of writing the publication is ongoing, as are the manuscripts that will be published published through mass media . Devotion team firmly underlines the cultural importance of implementing environmentally oriented Chemistry Practical Worksheets that use the potential of natural materials available around the home.